Effect of Iodine Loading on the Thyroid Hormone Level of Newborns Living in Kayseri Province - KORKMAZ, LEVENT; Kurtoglu, Selim; Bastug, Osman; Daar, Ghaniya; Halis, Hulya; Korkmaz, Levent; Memur, Seyma; Korkut, Sabriye; GÜNEŞ, TAMER; ÖZTÜRK, MEHMET ADNAN (My University, 2014)
Introduction Excessive iodine exposure during the fetal and neonatal periods can lead to neonatal hypothyroidism. This study was conducted to evaluate the level of iodine loading among newborns living in Kayseri province. A total of 59 newborns, who were admitted due to disorders in thyroid hormone levels, were included in the study.